PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN TAMU UNTUK MENGINAP DI HW HOTEL PADANG - ABDILLAH, MUHAMMAD; Kasmita, Kasmita; Abrian, Youmil Abrian (Journal of Home Economics and Tourism, 2014)
The purpose of research is to determine the Effects of Promoion mix to Guest Buyer Decision in HW Hotel Padang. This type of research is a comparative study causal. Population in the research amounted to 1400 people. Sampling technique is non probability sampling, using insidental sampling. Number of sample in this research amounted to 94 people. Data collection using a questionnaire based with the Likert scale that tested for validity and reliability.Â  Based on these results by using the t test showed that the five indicators of the promotion mix (Advertising, Personal selling, Sales promotion, Public relations, and Direct marketing) buyer decisions as the dependent variable significantly with the value of R square of 0.813.